Distribution Characteristics and Geogenic Mechanisms of Riverbed Overburden in Southwest China - Yan, Zongping; Xu, Mo; Kang, Xiaobing; Guo, Leilei; Zhang, Shishu (Frontiers in Earth Science, 2022)
The distribution, scale, and engineering geological characteristics of riverbed overburden have become one of the key issues in the construction of water conservancy and hydropower engineering projects in southwest China. In this study, we summarize and discuss the (variation of thickness) distribution and the genetic (formation) mechanisms of riverbed overburden in the associated rivers. This is done by compiling thickness data from constructed and planned dams. The results show that the overburden thickness is generally shallower in the upper Tibetan Plateau region, it is thickest in the marginal mountain region in the middle reaches, and shallower in the lower reaches of the mountain regions that are in contact with the Yunnan-Guizhou Plateau or Sichuan Basin. This holds true with the Distribution Law of shallow-thick-shallow. Additionally, the river overburden has the characteristic of thickening gradually from the basin edge to the plateau slope. Through the genesis, source, and distribution of the aggradation deposits in the riverbed, the genetic(formation) mechanisms of the river overburden layer is explored, and the coupling effect of tectonic-climatic-fluvial sedimentation processes on the variation of overburden thickness and spatial distribution is proposed. Finally, the geological problems encountered in engineering dams in thick overburden are analyzed, and common engineering measures are put forward. The results provide basic data support for the water resources exploitation and further development of river engineering in Southwest China.